Anticoagulation quality with warfarin therapy, and associated factors among adult outpatients at public hospitals in nekemte town, western Ethiopia: a retrospective study - Teka, Firafan Shuma; Korsa, Ayana Tadesse; Gebeyehu Bayisa, Habte; Befikadu W/Senbat, Dechasa; Shifera Beyene, Refisa; Dugassa Iticha, Dinka; Sefera Senbeta, Birbirsa (Frontiers in Pharmacology, 2025)
BackgroundThe global prevalence of poor anticoagulation control with warfarin therapy is high. Similarly, the quality of anticoagulation control with warfarin therapy in Ethiopia has been reported to be poor, with a notable paucity of data, especially in the western part of the country.ObjectivesThis study aimed to evaluate the anticoagulation quality, and associated factors among adult outpatients on warfarin therapy at Wallaga University Referral Hospital and Nekemte Comprehensive Specialized Hospital, Nekemte town, Western Ethiopia.MethodsA retrospective study was conducted at public hospitals in Nekemte town from June 1 to 31 July 2023. Data were collected by reviewing patients’ medical charts using a systematic random sampling technique. Time in the therapeutic range was determined using the Rosendaal method. The collected data were entered into EpiData version 4.6.0 and then exported to SPSS version 27.0 for analysis. Bivariable and multivariable logistic regression analyses were performed to identify significant associations. In the multivariable analysis, statistical significance was declared at a p-value of less than 0.05.ResultsA total of 402 patient medical charts with warfarin indications were reviewed. The mean age of the study participants was 38.9 ± 17.9 years, and 271 (67.4%) were female. Good warfarin anticoagulation quality was observed in 36 (9%) of the patients. Aspirin use (AOR = 2.685; CI: 0.872–10.277; p-value = 0.002) and congestive heart failure (AOR = 4.392; CI: 1.028–18.768; p-value = 0.046) were identified as independent predictors of poor anticoagulation quality.ConclusionAspirin use and congestive heart failure were independent predictors of poor anticoagulation quality with warfarin therapy.